Incidence of sexual dysfunction: a prospective survey in Ghanaian females - Amidu Nafiu; Owiredu William KBA; Woode Eric; Addai-Mensah Otchere; Quaye Lawrence; Alhassan Abass; Tagoe Edmond A (BMC, 2010)
Abstract Background Sexuality is a complex phenomenon that is being influenced by psychological as well as physiological factors. Its dysfunction includes desire, arousal, orgasmic and sex pain disorders. The present study aimed to assess the incidence of sexual dysfunction (SD) and related risk factors in a cohort of Ghanaian women. Method The Golombok Rust Inventory of Sexual Satisfaction (GRISS) was administered to 400 healthy women between 18 and 58 years old (mean +/- SD: 30.1 +/- 7.9) domiciled in the Kumasi metropolis. Results The response rate was 75.3% after 99 were excluded. Of the remaining 301 women, 50% were engaged in exercise, 26.7% indulge in alcoholic beverages and only 2% were smokers. A total of 62.1% of the women had attained high education, whilst, 28.9% were married. After logistic regression analysis, alcohol emerged (OR: 2.0; CI: 1.0 - 3.8; p = 0.04) as the main risk factor for SD. The overall prevalence of SD in these subjects was 72.8%. Severe difficulties with sexual function were identified in 3.3% of the studied population. The most prevalent areas of difficulty were anorgasmia (72.4%), sexual infrequency (71.4%), dissatisfaction (77.7%), vaginismus (68.1%), avoidance of sexual intercourse (62.5%), non-sensuality (61.5%) and non-communication (54.2%). Whereas 8% had severe difficulties with anorgasmia, only 6% had severe difficulties with vaginismus. Conclusion SD affects more than 70% of Ghanaian women who are sexually active. Alcohol significantly influences sexual activity.